Dampak Kegiatan Istighosah terhadap Kesehatan Mental di Masa Pandemi Covid-19 - Pitriani Pitriani; Ayi Rahman; Adnan Adnan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the effectiveness of istighosah activities at the Ar-Raaid Islamic boarding school on mental health during the pandemic. As it is known that the presence of Covid-19 has brought serious impacts such as anxiety and fear. The research method used is qualitative-descriptive with a thematic approach. Data were collected through interviews, observations, and literature review. The results of the study concluded that istighosah activities at the Ar-Raaid Islamic Boarding School had a good influence on mental health. The mentality of the students who were initially disturbed by the emergence of Covid-19 gradually improved along with regular istighosah. Istighosah has strengthened the students' belief that whatever happens is by Allah's will.